ANALISIS KINERJA USAHA KECIL DI KOTA MAKASSAR - Rukaiyah Rukaiyah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
In Indonesia Small businesses have a strategic position in the economy occurs mainly when the monetary and economic crisis in 1997/1998. According Mulyoutami et al . (2003 ) these types of businesses capable of facing exposure to storms of crisis and also has the ability to recover more quickly than larger business units. Small Business Personality significantly positive effect on the performance of Small Businesses amounted to 0.361 % . The higher the personality will be followed by an increase in the performance of Small Business in Makassar. Small Business Innovation significantly positive effect on the performance of Small Businesses amounted to 0.340 % . The higher the Small Business innovation will be followed by an increase in the performance of Small Business in Makassar